2023
DOI: 10.3390/fermentation9090828
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Stirring and Aeration Rate on Carotenoid Production in Yeast Rhodotorula toruloides CCT 7815 Envisioning Their Application as Soap Additives

Renata M. M. G. P. Ribeiro,
Bruno W. Picão,
Daniele O. Gonçalves
et al.

Abstract: The production of carotenoids by microbial organisms has gained significant interest due to the growing demand for natural products. Among the non-model oleaginous red yeasts, Rhodotorula toruloides stands out as an appealing host for natural carotenoid production. R. toruloides possesses the natural ability to metabolize a wide range of substrates, including lignocellulosic hydrolysates, and convert them into lipids and carotenoids. In this study, we focused on utilizing xylose, the main component of hemicell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…R. mucilaginosa MTCC-1403 produced the highest carotenoids in aerobic fermentation conditions (819.23 mg/g), compared to control (717.35 mg/g) [9]. Ribeiro et al [58] demonstrated that the highest carotenoid yields were achieved at high agitation rates (700 rpm) by R. toruloides. Aeration produces a concentration gradient, which may play an important role in fermentation efficiency.…”
Section: Agitationmentioning
confidence: 99%
“…R. mucilaginosa MTCC-1403 produced the highest carotenoids in aerobic fermentation conditions (819.23 mg/g), compared to control (717.35 mg/g) [9]. Ribeiro et al [58] demonstrated that the highest carotenoid yields were achieved at high agitation rates (700 rpm) by R. toruloides. Aeration produces a concentration gradient, which may play an important role in fermentation efficiency.…”
Section: Agitationmentioning
confidence: 99%